Carbon-nitrogen composite reinforced hardfacing flux-cored wire suitable for excavator bucket tooth, preparation method and carbon-nitrogen composite reinforcing method of excavator bucket tooth
By using carbon-nitrogen composite to strengthen wear-resistant surfacing flux core wire on the excavator bucket teeth, the problem of easy cracking of the bucket teeth is solved, the wear resistance and toughness are improved, and the repair effect is achieved with high hardness and low cost.
Patent Information
- Application Number
- CN202510566669.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2025-06-17
AI Technical Summary
The bucket teeth of existing excavators are prone to cracking, resulting in poor wear resistance, short service life and affecting working efficiency.
The carbon-nitrogen composite reinforced wear-resistant welding flux core wire material is used, including the flux core and the outer skin. The flux core is composed of carbon powder, chromium powder, titanium powder, manganese powder, silicon powder, nickel powder, titanium carbide powder, titanium nitride powder, vanadium powder, molybdenum powder and iron powder. The outer skin is H08A low-carbon steel belt, which is clad layer by layer on the excavator bucket teeth surface through MAG welding technology.
It improves the wear resistance and toughness of the excavator bucket teeth, and the surface hardness after welding can reach 63HRC. The weld is beautifully formed and basically has no collapse. It reduces production costs and extends the service life.
Smart Images

Figure CN120155688A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of processing welding materials, and relates to a carbonitride composite strengthened wear-resistant surfacing flux-cored wire applicable to the bucket teeth of an excavator. The present invention also relates to a preparation method of the above-mentioned carbonitride composite strengthened wear-resistant surfacing flux-cored wire applicable to the bucket teeth of an excavator. Background Art
[0002] After long-term operation, the bucket teeth of an excavator will all show wear, resulting in a serious reduction in working efficiency or even the machine being unable to work properly. As a vulnerable part of the key soil-contact component, surfacing the surface of the bucket teeth of an excavator can greatly improve the wear resistance of the soil-contact component. At the same time, the thickness of the surfacing layer is much thicker than the thin coating formed by other surface treatment technologies, which can resist the impact of hard objects and better protect the base material. Therefore, the wear-resistant surfacing technology has been more and more widely used in the excavator field, playing a key role in solving the problem of the wear failure and scrapping of the bucket teeth of an excavator, and can further improve the service life and operation efficiency of the bucket teeth.
[0003] For the complex environment during the operation of an excavator, not only excellent wear resistance is required for the bucket teeth of the excavator, but also relatively high requirements are placed on the mechanical properties of the bucket teeth of the excavator. Since the size of the primary M7C3 carbide in the Fe-Cr-C structure is relatively large, and the bonding performance between the carbide and the austenite matrix is poor, it is very easy to crack and spall on the surface of the surfacing layer, thereby reducing the service life of the bucket teeth of the excavator after surfacing. Therefore, in order to improve the service life of mechanical parts and avoid the shedding caused by the cracking of the surfacing alloy, it is of great significance to invent an Fe-Cr-C series wear-resistant surfacing flux-cored wire with good wear resistance, good toughness and not easy to crack. Summary of the Invention
[0004] The purpose of the present invention is to provide a carbonitride composite strengthened wear-resistant surfacing flux-cored wire applicable to the bucket teeth of an excavator, and solve the problem of easy cracking of traditional bucket teeth of an excavator in the prior art.
[0005] Another purpose of the present invention is to provide a preparation method of the above-mentioned carbonitride composite strengthened wear-resistant surfacing flux-cored wire applicable to the bucket teeth of an excavator.
[0006] The third purpose of the present invention is to provide a method for carbonitride composite strengthening of the bucket teeth of an excavator using the above-mentioned carbonitride composite strengthened wear-resistant surfacing flux-cored wire applicable to the bucket teeth of an excavator.
[0007] The first technical solution adopted by the present invention is a carbonitriding composite strengthened wear-resistant surfacing flux-cored wire for excavator bucket teeth, which includes a flux core and an outer skin. The flux core is composed of the following components by mass percentage: 3%-7% carbon powder, 16%-20% chromium powder, 4%-7% titanium powder, 0.6%-1.8% manganese powder, 0.5%-1.5% silicon powder, 2%-4% nickel powder, 9%-11% titanium carbide powder, 9%-11% titanium nitride powder, 1%-1.5% vanadium powder, 0.9%-1.2% molybdenum powder, and the rest is iron powder. The sum of the mass percentages of the above components is 100%.
[0008] Preferably, the outer skin is an H08A low-carbon steel strip with a width of 7 mm and a thickness of 0.4 mm.
[0009] Preferably, the powder filling rate of the flux core in the flux-cored wire is 23wt%-26wt%.
[0010] The second technical solution adopted by the present invention is a preparation method of a carbonitriding composite strengthened wear-resistant surfacing flux-cored wire for excavator bucket teeth. To prepare a carbonitriding composite strengthened wear-resistant surfacing flux-cored wire for excavator bucket teeth, the following steps are specifically implemented: Step 1: Weigh the following components by mass percentage respectively: 3%-7% carbon powder, 16%-20% chromium powder, 4%-7% titanium powder, 0.6%-1.8% manganese powder, 0.5%-1.5% silicon powder, 2%-4% nickel powder, 9%-11% titanium carbide powder, 9%-11% titanium nitride powder, 1%-1.5% vanadium powder, 0.9%-1.2% molybdenum powder, and the rest is iron powder. The sum of the mass percentages of the above components is 100%; Step 2: Place the weighed components in a heating furnace for heating. After drying the powder, place it in a powder mixer and mix thoroughly to obtain a flux core base material; Step 3: Use an H08A low-carbon steel strip as the outer skin. Wipe the end of the H08A low-carbon steel strip with anhydrous ethanol to remove the oil stains and dirt on the surface of the steel strip, and then put it into a tubular furnace for heat preservation; Step 4: Use the flux core base material and the outer skin obtained in Step 3 to make a flux-cored wire.
[0011] Preferably, in Step 2, the heating temperature in the heating furnace is 100℃-130℃, the heat preservation time is 2-3 hours, and the mixing time in the powder mixer is 1-2 hours.
[0012] Preferably, in Step 3, the heat preservation temperature of the tubular furnace is 150℃-200℃, the heat preservation time is 1h-1.5h, ensuring that the surface of the steel strip is clean and free of stains.
[0013] Preferably, Step 4 is specifically: Make the outer skin obtained in Step 3 into a U-shaped groove, and then add a flux core base material accounting for 23%-26% of the total weight of the flux-cored wire of the present invention into the U-shaped groove.
[0014] Close the U-shaped groove to wrap the flux-cored substrate therein, and draw it through a wire drawing die step by step to reduce the diameter until the requirement is met, generally preferably 1.2 mm. Subsequently, put the flux-cored wire into a tube furnace, keep the temperature at 150 °C - 200 °C, and keep it warm for 1 h - 1.5 h. After the heat preservation, wipe the surface of the welding wire with absolute ethanol.
[0015] The third technical solution adopted in the present invention is a carbonitriding strengthening method for the bucket teeth of an excavator, which uses a flux-cored wire for carbonitriding strengthening and wear-resistant surfacing suitable for the bucket teeth of an excavator, specifically: Load the prepared flux-cored wire into a fully automatic welding robot, select the bucket teeth of the excavator as the workpiece substrate, use a angle grinder to polish and remove the surface oxide scale and impurities, and make the surface smooth and flat. Subsequently, wipe the surfacing surface with absolute ethanol to ensure that the working platform is pollution-free. Use MAG welding as the heat source and clad layer by layer on the surface of the bucket teeth of the excavator to obtain a wear-resistant coating; the process parameters of MAG welding are: the welding speed is 0.21 m / min - 0.24 m / min, the welding current is 140 A - 170 A, the welding voltage is 19 V - 21 V, and the shielding gas is 80 vol% Ar + 20 vol% CO2.
[0016] The beneficial effects of the present invention are: (1) The flux-cored wire for carbonitriding strengthening and wear-resistant surfacing of the bucket teeth of the excavator in the present invention has high wear resistance and appropriate toughness.
[0017] (2) After the carbonitriding strengthening of the bucket teeth of the excavator using the flux-cored wire of the present invention, the surfacing on the surface of the bucket teeth of the excavator is beautiful in shape. After welding, the surface hardness can reach 63 HRC, which greatly improves the hardness of the iron-based wear-resistant coating, and has good bonding with the substrate and excellent mechanical properties.
[0018] (3) The present invention provides a method for repairing the bucket teeth of an excavator and improving its wear resistance with MAG welding as the heat source and the flux-cored wire as the raw material; during the repair process, there is less spatter, the arc is stable, the weld formation is beautiful, and there is basically no collapse phenomenon. In addition, the equipment required for repair is simple and the production cost is low; while obtaining high performance, the production cost is reduced. Description of the Drawings
[0019] Figure 1 It is the metallographic photograph of the wear-resistant surfacing layer of the bucket teeth of the excavator in Example 8 of the present invention. Detailed Description of the Invention
[0020] The following is a detailed description in combination with specific embodiments.
[0021] Example 1 The present invention relates to a flux cored wire for carbonitriding composite strengthening and wear-resistant surfacing of excavator bucket teeth, which comprises a flux core and an outer skin. The flux core is composed of the following components by mass percentage: 3%-7% carbon powder, 16%-20% chromium powder, 4%-7% titanium powder, 0.6%-1.8% manganese powder, 0.5%-1.5% silicon powder, 2%-4% nickel powder, 9%-11% titanium carbide powder, 9%-11% titanium nitride powder, 1%-1.5% vanadium powder, 0.9%-1.2% molybdenum powder, and the balance is iron powder. The sum of the mass percentages of the above components is 100%. The outer skin is an H08A low-carbon steel strip with a width of 7 mm and a thickness of 0.4 mm. The powder filling rate of the flux core in the flux cored wire is 23wt%-26wt%.
[0022] The basis for the chemical composition design of the flux cored wire of the present invention is as follows: C: Carbon and chromium are alloying elements that have a greater influence on the structure of high-chromium cast iron. As the mass fractions of carbon and chromium elements increase, the structure of high-chromium cast iron will change from hypoeutectic structure to hypereutectic structure, and the primary phase will change from austenite to M7C3 carbide. These hard phases have a high hardness, which can significantly improve the wear resistance of the surfacing layer.
[0023] Cr: Chromium element, as an important element to improve the corrosion resistance of materials, will form a dense chromium oxide film when reacting with oxygen. This oxide film attached to the surface effectively prevents the penetration of hydrogen. Chromium will also form a solid solution in steel, improving the hardness and strength of the material.
[0024] Mn: The main functions of adding manganese element include improving the mechanical properties of the weld: Manganese element can improve the hardness and strength of the weld, thus enhancing the mechanical properties of the welded joint. When the manganese content is between 0.6% and 1.8%, the weld metal has high strength and toughness.
[0025] Ti: Titanium is an active metal element with a strong affinity for non-metallic elements such as oxygen, sulfur, nitrogen, and carbon. When added to high-chromium cast iron, various reactions will occur, producing multiple effects. As the Ti content increases, both the primary carbide and the total carbide (primary carbide and eutectic carbide) are gradually refined, and the volume fraction of TiC also increases with the increase of Ti content. Moreover, TiC is mainly distributed near the M7C3 carbide. When the Ti content is too high, TiC will grow and agglomerate.
[0026] Ni: The main functions of adding Ni element include improving the corrosion resistance, hot cracking resistance, strength and toughness of the welded joint. Specifically: Improving hot cracking resistance: During the welding process, hot cracks are likely to appear in the welded joint during heating and cooling. The Ni element can effectively inhibit and reduce the occurrence of hot cracking, thus improving the hot cracking resistance of the welded joint. Improving strength and toughness: The addition of Ni element can endow the welded joint with certain strength and toughness, thereby increasing the service life and stability of the welded joint.
[0027] Si: The main functions of adding silicon element include deoxidation, preventing the generation of pores and optimizing the microstructure of the weld. Silicon is the most commonly used deoxidizing element in the welding wire. It can prevent iron from combining with oxygen and reduce FeO in the molten pool.
[0028] Mo: Molybdenum element also promotes the formation of the oxide film, thereby improving the corrosion resistance of the material. Molybdenum forms a solid solution in steel, and by refining the grains, the hardness and strength of the material are improved.
[0029] Nb: The main functions of adding niobium element include improving corrosion resistance and welding performance. Surfacing tests were carried out on 1Cr13 martensitic stainless steel by adding different contents of ferroniobium and ferrovanadium. The results show that as the contents of ferroniobium and ferrovanadium in the flux-cored wire increase, the number of precipitated phases in the surfacing deposited metal gradually increases. These precipitated phases are Nb- and V-containing carbonitrides, which can effectively inhibit the formation of Cr-rich precipitated phases and increase the effective Cr content in the matrix.
[0030] TiN: TiN has an NaCl-type crystal structure and a very small misorientation degree with ferrite, which promotes the heterogeneous nucleation of ferrite and refines the ferrite grain boundaries. The refinement of ferrite provides a large number of grain boundaries for the formation of GBA. Therefore, austenite preferentially forms in the form of GBA, and the amount of intragranular austenite decreases.
[0031] V: It has the following effects in high-Cr cast iron: The microhardness of VC formed after adding V can reach 2300 - 2800 HV, which is about twice the hardness of M7C3-type carbides in ordinary high-chromium cast iron. As V increases, the amount of VC increases, and the wear resistance of high-chromium cast iron improves. At the same time, V can refine the primary austenite. In the eutectic structure of VC + austenite, the distribution of VC is relatively uniform, and the reduction effect on the matrix toughness is less than that of M7C3 in the eutectic. Therefore, under the condition of equal carbide content, the V-containing high-chromium cast iron not only has high wear resistance but also better impact toughness.
[0032] Example 2 The preparation method of the flux-cored wire for carbonitriding composite strengthening wear-resistant surfacing of excavator bucket teeth applicable to the present invention. The preparation example 1 is applicable to the flux-cored wire for carbonitriding composite strengthening wear-resistant surfacing of excavator bucket teeth, and is specifically implemented according to the following steps: Step 1: Weigh the following components by mass percentage respectively: 3%-7% carbon powder, 16%-20% chromium powder, 4%-7% titanium powder, 0.6%-1.8% manganese powder, 0.5%-1.5% silicon powder, 2%-4% nickel powder, 9%-11% titanium carbide powder, 9%-11% titanium nitride powder, 1%-1.5% vanadium powder, 0.9%-1.2% molybdenum powder, and the rest is iron powder. The sum of the mass percentages of the above components is 100%; Step 2: Place the weighed components above in a heating furnace for heating. Place the dried powder in a powder mixer and mix well to obtain the flux cored base material. In Step 2, the heating temperature in the heating furnace is 100°C - 130°C, the heat preservation time is 2 - 3 hours, and the mixing time in the powder mixer is 1 - 2 hours; Step 3: Use H08A low-carbon steel strip as the outer skin. Wipe the end of the H08A low-carbon steel strip with anhydrous ethanol to remove the oil stains and dirt on the surface of the steel strip, and then place it in a tube furnace for heat preservation. In Step 3, the heat preservation temperature of the tube furnace is 150°C - 200°C, and the heat preservation time is 1h - 1.5h to ensure that the surface of the steel strip is clean and stain-free.
[0033] Step 4: Use the flux cored base material and the outer skin obtained in Step 3 to make the flux cored wire. Step 4 is specifically as follows: Make the outer skin obtained in Step 3 into a U-shaped groove, and then add the flux cored base material accounting for 23%-26% of the total weight of the flux cored wire of the present invention into the U-shaped groove. Close the U-shaped groove to wrap the flux cored base material inside, and draw and reduce the diameter through a wire drawing die one by one until the requirements are met, generally preferably 1.2 mm. Then place the flux cored wire in a tube furnace, the heat preservation temperature is 150°C - 200°C, and the heat preservation time is 1h - 1.5h. After the heat preservation is over, wipe the surface of the welding wire with anhydrous ethanol.
[0034] Example 3 The carbonitriding strengthening method for the bucket teeth of an excavator of the present invention uses a carbonitriding strengthening wear-resistant surfacing flux cored wire suitable for the bucket teeth of an excavator, specifically: Load the prepared flux cored wire into a full-automatic welding robot, select the bucket teeth of the excavator as the workpiece base material, use a angle grinder to polish and remove the surface oxide scale and impurities, make the surface smooth and flat, and then wipe the surfacing surface with anhydrous ethanol to ensure that the working platform is pollution-free. Use MAG welding as the heat source and clad layer by layer on the surface of the bucket teeth of the excavator to obtain a wear-resistant coating; the process parameters of MAG welding are: the welding speed is 0.21m / min - 0.24m / min, the welding current is 140A - 170A, the welding voltage is 19V - 21V, and the shielding gas is 80vol%Ar + 20vol%CO2.
[0035] Example 4 Step 1: Preparation method of a carbonitriding composite strengthened wear-resistant surfacing flux-cored wire for an excavator bucket tooth. Weigh the following raw material powders by mass percentage respectively: 4.0% carbon powder, 16.0% chromium powder, 4.0% titanium powder, 0.6% manganese powder, 0.5% silicon powder, 2.0% nickel powder, 9.0% titanium carbide powder, 9.0% titanium nitride powder, 1.0% vanadium powder, 0.9% molybdenum powder, and the rest is iron powder. The sum of the mass percentages of the above components is 100%; weigh the alloy powder by mass percentage using an electronic balance, and then use a V-shaped powder mixer to mix for 2 h to ensure thorough mixing. Subsequently, heat and keep warm in a tubular furnace under a pure argon atmosphere. The heat preservation temperature is 200 °C, and the heat preservation time is 1.5 h to remove the moisture in the alloy powder; Step 2: Use H08A low-carbon steel strip as the outer skin of the flux-cored wire. The width is 7 mm and the thickness is 0.4 mm. Wipe the end of the H08A low-carbon steel strip with anhydrous ethanol to remove the oil stains and dirt on the strip surface, and then put it into a tubular furnace. The heat preservation temperature is 200 °C, and the heat preservation time is 1.5 h to ensure that the strip surface is clean and stain-free; Step 3: Roll the low-carbon steel strip into a U-shaped groove, and then add flux-cored powder accounting for 23% of the total weight of the flux-cored wire of the present invention into the U-shaped groove. Close the U-shaped groove to wrap the flux-cored powder so that the powder will not leak out. Then, through a wire drawing die, draw and reduce the diameter step by step until it reaches 1.2 mm. Subsequently, put the welding wire into a tubular furnace. The heat preservation temperature is 1200 °C, and the heat preservation time is 1.5 h. After the heat preservation ends, wipe the surface of the welding wire with anhydrous ethanol to obtain a wear-resistant surfacing metal flux-cored wire.
[0036] Step 4: Load the prepared flux-cored wire into a fully automatic welding robot. Select the excavator bucket tooth as the workpiece base material. Use a angle grinder to polish and remove the surface oxide scale and impurities, and polish the surface flat and smooth. Then wipe the surfacing surface with anhydrous ethanol to ensure that the working platform is pollution-free. Use MAG welding as the heat source and layer by layer cladding on the surface of the excavator bucket tooth to obtain a wear-resistant coating. The process parameters of MAG welding are as follows: the welding speed is 0.22 m / min, the welding current is 150 A, and the welding voltage is 20 V. The shielding gas is 80 vol% Ar + 20 vol% CO2.
[0037] Example 5 Step 1: Preparation of flux-cored wire for improving the wear resistance of excavator bucket teeth. Weigh the following raw material powders by mass percentage: carbon powder 4.5%, chromium powder 17.0%, titanium powder 5.0%, manganese powder 0.8%, silicon powder 0.6%, nickel powder 3.0%, titanium carbide powder 8.0%, titanium nitride powder 9.0%, vanadium powder 1.0%, molybdenum powder 0.9%, and the rest is iron powder. The sum of the mass percentages of the above components is 100%; weigh the alloy powder by mass percentage using an electronic balance, and then use a V-shaped powder mixer to mix for 2 h to ensure thorough mixing. Subsequently, heat and keep warm in a tube furnace under an argon atmosphere. The holding temperature is 200 °C and the holding time is 1.5 h to remove the moisture in the alloy powder; Step 2: Use H08A low-carbon steel strip as the outer skin of the flux-cored wire, with a width of 7 mm and a thickness of 0.4 mm. Wipe the end of the H08A low-carbon steel strip with anhydrous ethanol to remove the oil stains and dirt on the strip surface, and then put it into a tube furnace. The holding temperature is 200 °C and the holding time is 1.5 h to ensure that the strip surface is clean and stain-free; Step 3: Roll the low-carbon steel strip into a U-shaped groove, and then add flux-cored powder accounting for 23% of the total weight of the flux-cored wire of the present invention into the U-shaped groove. Close the U-shaped groove to wrap the flux-cored powder so that the powder will not leak out. Then, through a wire drawing die, draw and reduce the diameter step by step until it reaches 1.2 mm, Subsequently, put the welding wire into a tube furnace. The holding temperature is 1200 °C and the holding time is 1.5 h. After the holding is completed, wipe the surface of the welding wire with anhydrous ethanol to obtain a wear-resistant surfacing metal cored wire.
[0038] Step 4: Load the prepared flux-cored wire into a fully automatic welding robot. Select the excavator bucket tooth as the workpiece substrate. Use a grinding wheel to polish and remove the surface oxide scale and impurities, and polish the surface to be flat and smooth. Then wipe the surfacing surface with anhydrous ethanol to ensure that the working platform is pollution-free. Use MAG welding as the heat source and clad layer by layer on the surface of the excavator bucket tooth to obtain a wear-resistant coating. The process parameters of MAG welding are as follows: welding speed is 0.22 m / min, welding current is 150 A, and welding voltage is 20 V. The shielding gas is 80 vol% Ar + 20 vol% CO2.
[0039] Example 6 Step 1: Preparation of flux-cored wire for improving the wear resistance of excavator bucket teeth. Weigh the following raw material powders by mass percentage: carbon powder 6.0%, chromium powder 19.0%, titanium powder 5.5%, manganese powder 1.0%, silicon powder 1.0%, nickel powder 3.0%, titanium carbide powder 10.0%, titanium nitride powder 9.0%, vanadium powder 1.0%, molybdenum powder 0.9%, and the rest is iron powder. The sum of the mass percentages of the above components is 100%; weigh the alloy powder by mass percentage using an electronic balance, and then mix it for 2 h using a V-shaped powder mixer to ensure thorough mixing. Subsequently, heat and keep it warm in a tube furnace under an argon atmosphere. The holding temperature is 200 °C, and the holding time is 1.5 h to remove the moisture in the alloy powder; Step 2: Use H08A low-carbon steel strip as the outer skin of the flux-cored wire, with a width of 7 mm and a thickness of 0.4 mm. Wipe the end of the H08A low-carbon steel strip with anhydrous ethanol to remove the oil stains and dirt on the strip surface, and then put it into a tube furnace. The holding temperature is 200 °C, and the holding time is 1.5 h to ensure that the strip surface is clean and stain-free; Step 3: Roll the low-carbon steel strip into a U-shaped groove, and then add flux-cored powder accounting for 23% of the total weight of the flux-cored wire of the present invention into the U-shaped groove. Close the U-shaped groove to wrap the flux-cored powder inside, ensuring that the powder does not leak out. Then, through a wire drawing die, draw and reduce the diameter step by step until it reaches 1.2 mm. Subsequently, put the welding wire into a tube furnace. The holding temperature is 1200 °C, and the holding time is 1.5 h. After the holding is completed, wipe the surface of the welding wire with anhydrous ethanol to obtain a wear-resistant surfacing metal flux-cored wire.
[0040] Step 4: Load the prepared flux-cored wire into a fully automatic welding robot. Select the excavator bucket tooth as the workpiece substrate. Use a angle grinder to polish and remove the surface oxide scale and impurities, and polish the surface smooth. Then wipe the surfacing surface with anhydrous ethanol to ensure that the working platform is pollution-free. Use MAG welding as the heat source and layer by layer cladding on the surface of the excavator bucket tooth to obtain a wear-resistant coating. The process parameters of MAG welding are as follows: welding speed is 0.22 m / min, welding current is 150 A, and welding voltage is 20 V. The shielding gas is 80 vol% Ar + 20 vol% CO2.
[0041] Example 7 Step 1: Preparation of flux-cored wire for improving the wear resistance of excavator bucket teeth. Weigh the following raw material powders by mass percentage: carbon powder 4.0%, chromium powder 16.5%, titanium powder 6.5%, manganese powder 1.0%, silicon powder 1.0%, nickel powder 3.0%, titanium carbide powder 10.0%, titanium nitride powder 9.0%, vanadium powder 1.4%, molybdenum powder 0.9%, and the rest is iron powder. The sum of the mass percentages of the above components is 100%; weigh the alloy powder by mass percentage using an electronic balance, and then mix it for 2 h using a V-shaped powder mixer to ensure thorough mixing. Subsequently, heat and hold it in a tube furnace under a pure argon atmosphere. The holding temperature is 200 °C, and the holding time is 1.5 h to remove the moisture in the alloy powder; Step 2: Use H08A low-carbon steel strip as the outer skin of the flux-cored wire, with a width of 7 mm and a thickness of 0.4 mm. Wipe the end of the H08A low-carbon steel strip with anhydrous ethanol to remove the oil stains and dirt on the strip surface, and then put it into a tube furnace. The holding temperature is 200 °C, and the holding time is 1.5 h, Ensure that the strip surface is clean and free of stains; Step 3: Roll the low-carbon steel strip into a U-shaped groove, and then add flux-cored powder accounting for 23% of the total weight of the flux-cored wire of the present invention into the U-shaped groove. Close the U-shaped groove to wrap the flux-cored powder so that the powder will not leak out. Then, through a wire drawing die, draw and reduce the diameter step by step until it reaches 1.2 mm. Subsequently, put the welding wire into a tube furnace. The holding temperature is 1200 °C, and the holding time is 1.5 h. After the holding is completed, wipe the surface of the welding wire with anhydrous ethanol to obtain a wear-resistant surfacing metal flux-cored wire.
[0042] Step 4: Load the prepared flux-cored wire into a fully automatic welding robot. Select the excavator bucket tooth as the workpiece substrate. Use a angle grinder to polish and remove the surface oxide scale and impurities, and make the surface smooth. Subsequently, wipe the surfacing surface with anhydrous ethanol to ensure that the working platform is pollution-free. Use MAG welding as the heat source and clad layer by layer on the surface of the excavator bucket tooth to obtain a wear-resistant coating. The process parameters of MAG welding are as follows: welding speed is 0.22 m / min, welding current is 150 A, and welding voltage is 20 V. The shielding gas is 80 vol% Ar + 20 vol% CO2.
[0043] Example 8 Step 1: Preparation of a flux-cored wire for improving the wear resistance of excavator bucket teeth. Weigh the following raw material powders by mass percentage: carbon powder 4.8%, chromium powder 18.5%, titanium powder 4.5%, manganese powder 1.8%, silicon powder 1.0%, nickel powder 3.6%, titanium carbide powder 11.0%, titanium nitride powder 11.0%, vanadium powder 1.4%, molybdenum powder 0.9%, and the rest is iron powder. The sum of the mass percentages of the above components is 100%; weigh the alloy powder by mass percentage using an electronic balance, and then use a V-shaped powder mixer to mix for 2 h to ensure thorough mixing. Subsequently, heat and hold in a tubular furnace under a pure argon atmosphere. The holding temperature is 200 °C, and the holding time is 1.5 h to remove the moisture in the alloy powder; Step 2: Use H08A low-carbon steel strip as the outer skin of the flux-cored wire, with a width of 7 mm and a thickness of 0.4 mm. Wipe the end of the H08A low-carbon steel strip with anhydrous ethanol to remove the oil stains and dirt on the strip surface, and then put it into a tubular furnace. The holding temperature is 200 °C, and the holding time is 1.5 h to ensure that the strip surface is clean and stain-free; Step 3: Roll the low-carbon steel strip into a U-shaped groove, and then add flux-cored powder accounting for 23% of the total weight of the flux-cored wire of the present invention into the U-shaped groove. Close the U-shaped groove to wrap the flux-cored powder so that the powder will not leak out. Then, through a wire drawing die, draw and reduce the diameter step by step until it reaches 1.2 mm. Subsequently, put the welding wire into a tubular furnace. The holding temperature is 1200 °C, and the holding time is 1.5 h. After the holding is completed, wipe the surface of the welding wire with anhydrous ethanol to obtain a wear-resistant surfacing metal flux-cored wire.
[0044] Step 4: Load the prepared flux-cored wire into a fully automatic welding robot. Select the excavator bucket tooth as the workpiece substrate. Use a angle grinder to polish and remove the surface oxide scale and impurities, and polish the surface flat and smooth. Then wipe the surfacing surface with anhydrous ethanol to ensure that the working platform is pollution-free. Use MAG welding as the heat source and gradually clad it on the surface of the excavator bucket tooth to obtain a wear-resistant coating. The process parameters of MAG welding are as follows: the welding speed is 0.22 m / min, the welding current is 150 A, and the welding voltage is 20 V. The shielding gas is 80 vol% Ar + 20 vol% CO2.
[0045] The wear-resistant coating on the surface of the excavator bucket tooth obtained in Example 8 of the present invention has a beautiful shape and less spatter; uniformly distributed reinforcing phases are formed; through testing, the average hardness of the wear-resistant coating on the surface of the excavator bucket tooth can reach about 67 HRC, and the shear strength with the substrate can reach 623 MPa; Figure 1 This is the metallographic diagram at the bonding interface between the surfacing layer and the substrate. It can be seen that good metallurgical bonding with the substrate is achieved, realizing high-hardness wear resistance of the surfacing layer while achieving firm bonding with the substrate, reducing the repair cost, and having economic benefits.
Claims
1. Carbon-nitrogen composite reinforced wear-resistant surfacing flux-cored wire suitable for excavator bucket teeth, characterized in that: The invention comprises a core and an outer skin, wherein the core is composed of the following components in mass percentage: 3%-7% carbon powder, 16%-20% chromium powder, 4%-7% titanium powder, 0.6%-1.8% manganese powder, 0.5%-1.5% silicon powder, 2%-4% nickel powder, 9%-11% titanium carbide powder, 9%-11% titanium nitride powder, 1%-1.5% vanadium powder, 0.9%-1.2% molybdenum powder, and the rest is iron powder, and the sum of the mass percentages of the above components is 100%.
2. The carbon-nitrogen composite reinforced wear-resistant surfacing flux-cored wire suitable for excavator bucket teeth according to claim 1, characterized in that: The outer skin is H08A low-carbon steel strip with a width of 7 mm and a thickness of 0.4 mm.
3. The carbon-nitrogen composite reinforced wear-resistant surfacing flux-cored wire suitable for excavator bucket teeth according to claim 2, characterized in that: The filling rate of the core powder in the core wire is 23wt%-26wt%.
4. A method for preparing a carbon-nitrogen composite reinforced wear-resistant surfacing flux-cored wire suitable for excavator bucket teeth, characterized in that: The preparation of the carbon-nitrogen composite reinforced wear-resistant surfacing flux-cored wire suitable for excavator bucket teeth as claimed in claim 3 is specifically carried out according to the following steps: Step 1: Weigh the following components by mass percentage: carbon powder 3%-7%, chromium powder 16%-20%, titanium powder 4%-7%, manganese powder 0.6%-1.8%, silicon powder 0.5%-1.5%, nickel powder 2%-4%, titanium carbide powder 9%-11%, titanium nitride powder 9%-11%, vanadium powder 1%-1.5%, molybdenum powder 0.9%-1.2%, and the rest is iron powder. The sum of the mass percentages of the above components is 100%; Step 2: Heat the components weighed above in a heating furnace, and place the dried powder in a powder mixer to fully mix to obtain a drug core matrix; Step 3: Use H08A low-carbon steel strip as the outer skin, wipe the H08A low-carbon steel strip with anhydrous ethanol to remove the oil stains and dirt on the surface of the steel strip, and then put it into a tube furnace for heat preservation; Step 4: Use the core substrate and the outer skin obtained in step 3 to make a core wire.
5. The method for preparing the carbon-nitrogen composite reinforced wear-resistant surfacing flux-cored wire suitable for excavator bucket teeth according to claim 4, characterized in that: In the step 2, the heating temperature in the hot furnace is 100° C.-130° C., the heat preservation time is 2-3 hours, and the mixing time in the powder mixer is 1-2 hours.
6. The method for preparing the carbon-nitrogen composite reinforced wear-resistant surfacing flux-cored wire suitable for excavator bucket teeth according to claim 5, characterized in that: In the step 3, the insulation temperature of the tubular furnace is 150° C.-200° C., and the insulation time is 1 h-1.5 h, to ensure that the surface of the steel strip is clean and free of stains.
7. The method for preparing the carbon-nitrogen composite reinforced wear-resistant surfacing flux-cored wire suitable for excavator bucket teeth according to claim 6, characterized in that: The step 4 is specifically as follows: The outer skin obtained in step 3 is made into a U-shaped groove, and then a core base material accounting for 23%-26% of the total weight of the core wire material of the present invention is added into the U-shaped groove; Close the U-shaped groove to wrap the flux core substrate in it, and pass it through the wire drawing die to draw it step by step and reduce the diameter until it meets the requirements, generally preferably 1.2mm. Then put the flux core wire into a tubular furnace with a holding temperature of 150℃-200℃ and a holding time of 1h-1.5h. After the holding is completed, wipe the surface of the welding wire with anhydrous ethanol.
8. A carbon-nitrogen composite strengthening method for excavator bucket teeth, characterized in that: The carbon-nitrogen composite reinforced wear-resistant surfacing flux-cored wire material suitable for excavator bucket teeth according to claim 7 is specifically: The prepared flux-cored wire is loaded into a fully automatic welding robot, the excavator bucket tooth is selected as the workpiece substrate, and an angle grinder is used to remove surface oxide scale and impurities, and the surface is polished flat and smooth. Then, anhydrous ethanol is used to wipe the surfacing surface to ensure that the working platform is pollution-free. MAG welding is used as the heat source to melt the surface of the excavator bucket tooth layer by layer to obtain a wear-resistant coating; the process parameters of MAG welding are: welding speed is 0.21m / min-0.24m / min, welding current is 140A-170A, welding voltage is 19V-21V, and shielding gas is 80vol%Ar+20vol%CO2.